Successful budgeting for small business - Cheng, Yafang (2006)
The most important rule for financial management in small companies, although it is general rule for all sizes of company, is not to run out of cash. Being a financial manager for a small company, it is more serious to manage company's budget because the smaller enterprise faces greater challenge in raising cash.